Climate change risks illustrated by the Intergovernmental Panel on Climate Change (IPCC) “burning embers” - P. Marbaix; P. Marbaix; P. Marbaix; A. K. Magnan; A. K. Magnan; A. K. Magnan; V. Muccione; V. Muccione; P. W. Thorne; Z. Zommers (Earth System Science Data)
The completion of the Sixth Assessment Cycle of the Intergovernmental Panel on Climate Change (IPCC) provides a unique opportunity to understand where the world stands on climate-change-related risks to natural and human systems at the global level, as well as for specific regions and sectors. Since its Third Assessment Report (AR3), released 2 decades ago, the IPCC has developed a synthetic representation of how risks increase with global warming, with risk levels reflected by the colours used, including shades of yellow and red, which led to the nickname “burning embers”. While initially designed to illustrate five overarching Reasons for Concern, these diagrams have been progressively applied to risks in specific systems and regions over the last 10 years. However, the information gathered through expert elicitation and the resulting quantitative risk assessments have hitherto remained scattered within and across reports and specific data files. This paper overcomes this limitation by developing a database containing all embers from AR3 to AR6 and an associated online “Climate Risks Embers Explorer” (CREE) to facilitate the exploration of the assessed risks. The data are also available in an archive file in a widely accessible format (https://doi.org/10.5281/zenodo.12626976, Marbaix et al., 2024). Important aspects of data homogenization are discussed, and an approach to structuring information on assessed risk increases is presented. Potential uses of the data are explored through aggregated analyses of risks and adaptation benefits, which show that, excluding high-adaptation cases, half of the assessed risk levels increase from a moderate risk to a high risk between 1.5 and 2 to 2.3 °C of global warming, a result which is consistent with the separate assessment of the Reasons for Concern by the IPCC. The database lays the groundwork for future risk assessments and the development of burning embers by providing a standardized baseline of risk data. It also highlights important areas for improvement in the forthcoming Seventh Assessment Cycle of the IPCC, particularly towards the systematic, homogeneous, and structured collection of information on illustrated risk increases; comprehensive coverage of impacted regions; a systematic consideration of adaptation and/or vulnerability levels; and, possibly, the coverage of risks from response measures. In the context of an ever-growing body of literature and knowledge, the facility described herein has the potential to help in synthesizing and illustrating risks across scales and systems in a more consistent and comprehensive way.